A review on prebiotics and probiotics for the control of dysbiosis: present status and future perspectives. (22nd October 2014) - Ducatelle, R.; Eeckhaut, V.; Haesebrouck, F.; Van Immerseel, F.
<x content-type="archive" xml:space="preserve">Abstract</x> Dysbiosis or dysbacteriosis is defined as a shift in the intestinal microbiota composition resulting in an imbalance between beneficial and harmful bacteria. Since the ban on the use of growth-promoting antibiotics in animal feed in the EU, dysbiosis has emerged as a major problem in intensive animal production. Prebiotics and probiotics are currently under investigation as possible alternatives to growth-promoting antibiotics, as their mode of action is thought to be based largely on a modulation of the composition and function of the intestinal microbiota. In this review, we analyse the currently available data from both animal and human nutrition that document the potential and limitations of prebiotics and probiotics for the control of dysbiosis. An impressive number of empirical feeding trials have been carried out in healthy animals, yielding sometimes contradictory results. More in-depth studies have revealed the complexity of the interactions taking place in the lower intestinal tract, thus illustrating that pre- and probiotics cannot be a simple replacement for growth-promoting antibiotics. Although there are indications that the strategic use of pre- and probiotics can provide major benefits, there is still a lack of basic knowledge on the delicate interactions between the microbiota, the host and the feed components, which hampers the widespread use of these valuable feed additives.